Arthropod Borne Diseases - Marcondes, Carlos Brisola; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Arthropod borne diseases cause enormous morbidity and mortality in most countries, mostly in those situated in tropical areas, but also in temperate regions. This book provides organized information on all arthropod related diseases, to prevent suffering and deaths, for medical students and professionals. Since arthropod borne diseases are present in many regions of the world and can even surprise professionals and lays in non-endemic regions, like malaria in UK and Canada, the author and its many expert collaborators are sure that it will be essential in all hospitals, clinics and medical libraries around the world. As arthropod borne diseases of domesticated animals are very numerous and in some cases related to human diseases, they are also included in the book.
1. General comments and importance of arthropod-related diseases -- 2. Epidemiology of vector-borne diseases -- 3. Blood sucking insects and history -- 4. Blood sucking, vector-parasite relationship and transmission of diseases -- 5. Generalities on arboviruses -- 6. Yellow fever -- 7. Dengue -- 8. Other flaviviruses -- 9. Togaviridae -- 10. Bunyaviruses -- 11. Plague and tularemia -- 12. Rickettsial infections, Bartonella infections and coxiellosis -- 13. Borreliosis: Lyme disease and relapsing fever -- 14. Ehrlichiosis -- 15. Anaplasmosis -- 16. Leishmaniasis -- 17. American trypanosomiasis (Chagas disease) -- 18. Sleeping sickness, nagana -- 19. Other trypanosomiasis -- 20. Malaria -- 21. Babesiosis -- 22. Theileriosis -- 23. Hepatozoonosis -- 24. Lymphatic filariasis -- 25. Onchocerciasis -- 26. Mansonelliasis -- 27. Dirofilariasis -- 28. Loiasis -- 29. Thelaziosis (canine eye-worm) -- 30. Habronemosis -- 31. Flies -- 32. Sucking and biting lice -- 33. Fleas -- 34. Diseases caused by Acari (ticks and mites) -- 35. Other irritating Arthropods (beetles, bugs, centipedes etc.) -- 36. Allergy to bites of hematophagous arthropods -- 37. Geoprocessing and expected distribution of diseases (including deforestation, global warming and other changes) -- 38. Wolbachia: influence on pathogeny, treatment and control of arthropod borne diseases.
Keywords: Medicine; Parasitology; Infectious diseases; Pathology; Entomology; Medicine & Public Health; Infectious diseases; Parasitology; Pathology; Entomology; Veterinary Medicine/Veterinary Science